Thermodynamic and Kinetic Control on the Formation of Two Novel Metal-Organic Frameworks Based on the Er(III) Ion and the Asymmetric Dimethylsuccinate Ligand - Bernini, María Belén (2010)
Two new layered polymeric frameworks have been synthesized under different hydrothermal conditions and characterized by single-crystal X-ray diffraction, thermal analysis, and variable temperature-Fourier Transform Infrared Spectroscopy (VT-FTIR). The compound I, with formula [Er2(dms)3(H2O)4], has a triclinic cell with parameters a = 5.8506 Å, b = 9.8019 Å, c = 11.9747 Å, α = 70.145°, β = 80.234°, and γ = 89.715°, and the compound II, [Er2(dms)3(H2O)], is monoclinic and its cell parameters are a = 11.1794 Å, b = 18.2208 Å, c = 12.7944 Å, β = 112.4270°, where dms = 2,2-dimethylsuccinate ligand. A theoretical study including energy calculations of the dms conformers was carried out at the Density Functional Theory (DFT-B3LYP) level of theory, using the 6-311G* basis set. Further calculations of the apparent formation energies of I and II crystalline structures were performed by means of the periodic density functional theory, using DF plane-waves. The analysis of the structural features, theoretical relative stabilities, and the influence of synthesis conditions are presented here. The heterogeneous catalytic activity of the new compounds is tested and reported.